The Faiths of the Postwar Presidents : From Truman to Obama - Holmes, David L. (David Lynn) (Book collections on Project MUSE., 2012)
The Faiths of the Founding Fathers, an acclaimed look at the spiritual beliefs of such iconic Americans as Franklin, Washington, and Jefferson, established David L. Holmes as a measured voice in the heated debate over the new nation's religious underpinnings. With the same judicious approach, Holmes now looks at the role of faith in the lives of the twelve presidents who have served since the end of World War II. Holmes examines not only the beliefs professed by each president but also the variety of possible influences on their religious faith, such as their upbringing, education, and the faith of their spouse. In each profile close observers such as clergy, family members, friends, and advisors recall churchgoing habits, notable displays of faith (or lack of it), and the influence of their faiths on policies concerning abortion, the death penalty, Israel, and other controversial issues. Whether discussing John F. Kennedy's philandering and secularity or Richard Nixon's betrayal of Billy Graham's na?ve trust during Watergate, Holmes includes telling and often colorful details not widely known or long forgotten. We are reminded, for instance, how Dwight Eisenhower tried to conceal the background of his parents in the Jehovah's Witnesses and how the Reverend Cotesworth Lewis's sermonizing to Lyndon Johnson on the Vietnam War was actually not a left- but a right-wing critique. National interest in the faiths of our presidents is as strong as ever, as shown by the media frenzy engendered by George W. Bush's claim that Jesus was his favorite political philosopher or Barack Obama's parting with his minister, the Reverend Jeremiah Wright. Holmes's work adds depth, insight, and color to this important national topic.